THE ENGLISH LANGUAGE AND ITS RELEVANCE IN THE MODERN WORLD - Axmatova Farangiz, (TADQIQOTLAR, 2026)
Annotation: This article explores the growing importance and relevance of the English language in the  modern globalized  world. English  has  become  a  universal means  of  communication  in  education,  science,  technology,  business,  tourism,  and diplomacy.  The  paper  discusses  the  historical  development  of  English,  its transformation  into  a  global  lingua  franca,  and  its  influence  on  international cooperation.